This sea of darkness, craziness and opportunity': students experiences of depression and social identities at a South African university - Craig, Ashleigh (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
This study explores how the interaction between depression and social identities is experienced by South African university students. Semi-structured interviews were conducted with eight students at Rhodes University who have had depressive experiences and analysed using Interpretative Phenomenological Analysis. The following five superordinate themes emerged out of the data: 1) the self looking in, 2) the self looking out, 3) the misunderstood self, 4) the student self and 5) the loss of self. Findings showed that students' depression is significantly influenced by their social identities, which are experienced as multi-faceted and ever-changing within the university context. The related therapeutic implications are also discussed.
Keywords: Depression, Mental -- South Africa -- Makhanda; Depression in adolescence -- South Africa -- Makhanda; College students -- Mental health -- South Africa -- Makhanda; Group identity -- South Africa -- Makhanda; Phenomenological psychology; Education, Higher -- Social aspects -- South Africa; Rhodes University